Land-use conflicts and quality on the coastal area "Bassin d'Arcachon": a regional newspapers analysis - Clarisse Cazals; Marie Lemarié (European Regional Science Association (ERSA), 2010)
In the economic context of standardized products some territories have been forced or chose to develop productions of specific quality goods based on the preservation and the value of local specificities (HIRCZAK, 2007). So, the question of quality has territorial and social dimensions. Knowing that coastal areas are sought-after territories by some actors with different perceptions, practices and economic objectives, it is increasingly difficult to agree on the attributes of the quality to preserve and develop on these areas. Indeed, we assume that the actors coordination on a territory can not be effective without a confrontation between different interests or logics. Equally, we assume that confrontations may generate land use conflicts, innovations and institutional changes. So, this work is linked to the economy of quality by focusing on what's going on just before actors coordination, that-is on the land use conflicts (LAGRANGE, VALCESCHINI, 2009). In this paper, we study these conflicts on an institutional territory in the southern France, the "Pays du Bassin d'Arcachon Val de l'Eyre (BAVE)" that associates urban with rural areas, coastal towns and forested inland. It is characterized by the diversity of the resources which can generate quality, as well as by the values associated to each of them. In this context, land use conflicts analysis shows different conceptions of quality on one territory (quality products, water quality, life quality). Indeed, this diversity reveals the different forms of coordination that are possible on one territory which are going to be interpreted in terms of conventions (MURDOCH & al., 2000; EYMARD-DUVERNAY, 2002,). To examine these conflicts, we make use of the land use conflicts analysis method created by the "Proximity" team of the UMR INRA SAD-APT. This method aims at revealing these conflicts by three complementary data sources: expert interviews, cases and regional daily press (TORRE & al., 2006). In this paper we expose the textual analysis results of the regional articles newspapers which constitute one of the three sources. They generate a global and synthetic vision of the conflicts on the "Pays BAVE".
Keywords: 330